The art of collage and its applications in the structure of fashion fabric designs (Al-Academy, 2024)
Fashion design is the procedural work that interprets the shape of the fabric into shapes, configurations, performance, and procedures that replace the shapes by cutting and pasting with unfamiliar ones that arouse astonishment and transform the finished design of the fabric into different fashions of an aesthetic and functional nature. The art of collage is one of the modern arts that artists have resorted to to break from the classical artistic schools and invent a new style of design by using natural elements and various materials and adapting them to reach the final form of the design. This research studies (the art of collage and its applications in the structures of fashion fabric designs). In light of this, the research is divided into four chapters.The first chapter included the methodological framework, the research problem and the need for it, and centered on launching the following question: What are the applications of collage art to the structures of fashion fabric design? Then, the importance of the research and its limitations. The chapter concluded with a definition of terms. The second chapter included the theoretical framework and was divided into two sections. The first section was about the art of collage in designing fabrics and fashions. The second section was about the effectiveness of the design structures of collage art in designing fabrics and fashions.The third chapter includes the research procedures, through the research community and its models represented by a group of 3 selected samples, while the fourth chapter includes the results, their discussion, conclusions, and sources.